2001
DOI: 10.1016/s0014-5793(01)02139-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of a proline‐induced broken‐helix motif in α‐helix 2 of Bacillus thuringiensis δ‐endotoxins

Abstract: Bacillus thuringiensis N N-endotoxins (Cry proteins), are widely used for insect control and plant protection. They are water-soluble proteins that insert into membranes forming ion channels. In most Cry toxins K K-helix 2 is broken by a highly conserved proline residue (Pro70 in Cry1Ab), generating a broken-helix motif. The flexibility of the motif was altered through site-directed mutagenesis. It was found that increasing the flexibility of the motif decreased the stability, the ion transport ability and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…These studies did not address the fate of regions of the toxin other than the ␣-helices of domain I once the toxin is inserted. However, proteinase K protection studies (typically used for detecting the regions of membrane proteins inside lipid bilayer) have shown that a 60-kDa form (or higher molecular weight aggregate) of the toxin has been protected in membranes (15,18,19,31,35). This suggests that most of the toxin was likely to be embedded in the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies did not address the fate of regions of the toxin other than the ␣-helices of domain I once the toxin is inserted. However, proteinase K protection studies (typically used for detecting the regions of membrane proteins inside lipid bilayer) have shown that a 60-kDa form (or higher molecular weight aggregate) of the toxin has been protected in membranes (15,18,19,31,35). This suggests that most of the toxin was likely to be embedded in the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The partitioning rate of every mutant into the brush border membrane and artificial membranes are Entire Crystal Toxin Inserts into BBMV not the same. We have seen that mutagenesis of Phe-371 to other residues in decreasing order of hydrophobicity have compromised its insertion ability (31,34). Although mutation to Trp retained most of the toxicity of the toxin in these studies, the difference in the amount protected for this mutant (Fig.…”
Section: Expression and Purification Of The Toxin Mutants-cysteinementioning
confidence: 99%
See 1 more Smart Citation
“…However, we cannot rule out the possibility that buried disulfide bridges may not be exposed to the reducing environment of the midgut lumen. In this case, a plausible explanation is that the entire domain I inserts into membrane as previously proposed, either as a whole protein [7,[12][13][14][15][16][17] or as a member of an oligomeric complex [18,23,35,36]. This would also result in no difference in toxicity between the wild-type and disulfide proteins.…”
Section: Discussionmentioning
confidence: 70%
“…Both models involve separation of the α-helices from the α-helical bundle, followed by their insertion into the target membranes resulting in the formation of ion pores. Other studies have proposed that the whole domain I inserts into the protein, without α-helical separation [7,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%